Molecular Docking Study of Chalcone Analogue Compounds with Hydroxy and Methoxy Subtituents as Bcl-2 Inhibitors - Frimayanti, Neni; Dona, Rahma; Solihin, Tabah (Chempublish Journal, 2023)
Molecular docking study of 6 chalcone analogues with protein target from the crystallographic structure modeling of Bcl-2 protein with PDB code 2W3L was carried out using computational media using the Molecular Operating Environment (MOE) program. The aim of this study is to determine the potentiality of the 6 chalcone analogue compounds as Bcl-2 inhibitors using molecular docking studies. In this study, venetoclax was used as positive control. Based on docking results, binding free energy was used as information to know which wheather chalcone analogue compounds are active or not as Bcl-2 inhibitors. According to the docking results that have been carried out, it showed that the 6 chalcone analogue compounds have no potential as Bcl-2 inhibitors. Due to the superimposition of the 6 compounds that did not stick to the positive control and most importantly the binding free energy values ​​(S) of the 6 chalcone analogue compounds were higher than the binding free energy values ​​of the positive control (Venetoclax).